The Complete Project Manager : Integrating People, Organizational, and Technical Skills. - Englund, Randall (Berrett-Koehler Publishers, Incorporated, 2019)
The Complete Project Manager, 2nd Edition updates a respected textbook on project management soft skills to include project management's most vital new trends: agile methods, delivering business value, respecting ethics, and managing diversity. This is a classic, bestselling, practical guide that addresses the "soft" project management skills that are so essential to successful project, program, and portfolio management. Through a storytelling approach, the authors explain the necessary skills and how to use them to create an environment that supports project success. They demonstrate both the "why" and the "how" of creatively applying soft project management skills in the areas of leadership, conflict resolution, negotiations, change management, and more. This second edition features new sections on ethics, business analysis, agile project management, managing across generations and between cultures, and more. Skills like leadership, negotiations, conflict management, and navigating organizational politics have always been important for project managers who want to succeed. Now the authors show how you can adjust and hone those skills given the forces and trends in today's business world.